Software Engineering Handbook - Keyes, Jessica (CRC Press, 2009)
Unfortunately, much of what has been written about software engineering comes from an academic perspective which does not always address the everyday concerns that software developers and managers face. With decreasing software budgets and increasing demands from users and senior management, technology directors need a complete guide to the subject of software engineering. The successor to the bestselling Software Engineering Productivity Handbook, this book fulfills that need.